Research Advances in the Pathogenesis of Non-Alcoholic Fatty Liver Disease - Zhu, Chen; Deng, Zhengming (Journal of Contemporary Medical Practice, 2025)
Non-alcoholic fatty liver disease (NAFLD) is a chronic metabolic disorder characterized by hepatic steatosis. Its prevalence continues to rise against the backdrop of metabolic syndrome and obesity, posing a significant public health threat. Recent advancements in metabolomics, single-cell sequencing, and gene-editing technologies have greatly enhanced our understanding of NAFLD pathogenesis. This article reviews the latest research progress on NAFLD mechanisms, focusing on metabolic dysregulation, inflammatory responses, endoplasmic reticulum (ER) stress, and gut microbiota dysbiosis.